Entrance to the Garbhagriha of the Vishnu Temple - Temples of India Project Team (Jio Institute, 2024)
The lower section of the garbhagriha (sanctum sanctorum) entrance of the Vishnu Temple displays the river goddesses, Ganga and Yamuna, succeeded by a chauri (fly whisk) bearer, and then the Vaishnava dvarapalas (door guardians). These four-armed dvarapalas are depicted holding a gada (mace), a shankha (conch shell), a chakra (discus), and one of their hands are positioned in abhayahasta (a hand pose indicating reassurance or protection from fear). They are adorned with a karand mukuta (tiered crown), long garlands, and elaborate jewelry.